Influences of climate variability on cocoa health and productivity in agroforestry systems in Ghana - Asitoakor, B.K.; Asare, R.; Raebild, A.; Ravn, H.P.; Eziah, V.Y.; Owusu, K.; Mensah, E.O.; Vaast, Philippe (Elsevier, 2022)
The susceptibility of cocoa to harsh climatic conditions is evident in cocoa growing areas in Ghana, and climate distribution models show reduced cocoa suitability to climate change. We assessed how cocoa health and productivity were affected by varying climate conditions for 4 years in 23 cocoa farms along a gradient of low rainfall/high temperature in the north to high rainfall/low temperature in the south of Ghana's cocoa belts. Twenty cocoa trees per farm (in total 460) were observed and scored for their canopy condition, flower intensity, and damaged pods due to mirids, cocoa shield bugs, and black pod disease (BPD). Harvested pods and extracted dried cocoa beans were evaluated to ascertain yield/productivity. Insect pest damages to pods were on average 2.3 ± 0.8, 2.2 ± 1.0, and 3.0 ± 0.7 pods tree−1 year−1 in the south, middle and north, respectively. The healthiest and highest yielding trees were in the rainy south at 0.99 ± 0.02 kg dry beans tree−1 followed by the middle (0.84 ± 0.02 kg) and the north (0.60 ± 0.01 kg). BPD infection was highest in the south at 1.1 ± 1.1 pods tree−1 year−1, followed by the middle (0.7 ± 0.8), and the north (0.4 ± 0.6). Within sites variability in rainfall and temperature was not found to affect yields significantly. The variability in cocoa performance and occurrence of pests and diseases observed within sites may thus be caused by farm management practices that are key to the enhancement of productivity at site level. We recommend regular pruning of cocoa and shade trees to increase aeration and prevent BPD in high rainfall areas, and an increase in shade tree components in dry regions for insect pest management in cocoa systems.